Preparation and characterization of liposomes encapsulating Calophyllum inophyllum oil - Huu Trong Phan; Van Thanh Tran (Vietnam Journal of Science, Technology and Engineering, 2017)
Callophyllum inophyllum oil, also known as Tamanu oil, is reported to treat a wide range of skin problems such as acne, eczema, psoriasis, herpes, hemorrhoids, and injuries caused due to wounds, among others. Liposomes, which are effective carriers for topical treatment of dermal diseases, could enhance the therapeutic efficiency of Tamanu oil. Therefore, the purpose of this study was to formulate and characterize liposomes loading Tamanu oil. Liposomes encapsulating Tamanu oil with different ratios of Phospholipon 90G and L-α-lecithin were prepared using the thin-film hydration technique. Liposomal formulations were characterized in terms of aspect, particle size, size distribution, zeta potential, and morphology by using light microscope and dynamic light scattering analysis (DLS). Furthermore, the best formulation was tested with the storage stability after 30 days, and Tamanu oil loaded in the liposomes was identified as dictated in Vietnamese pharmacopoeia. The data demonstrated that an average liposome diameter of 53 nm with a narrow polydispersity (0.289) was obtained at a Phospholipon 90G to L-α- lecithin molar ratio of 4:6, and a Tamanu oil to phospholipid mass ratio of 1:3 approximately. In addition, according to the DLS results, the particle size and the zeta potential were quite stable at 2-8oC during 30 days of storage. The study achieved the promising results for developing a novel formulation containing Tamanu oil, which may be valuable to treatment of skin diseases.